A growth model with qualities, varieties, and human capital: stability and transitional dynamics - Sequeira, T. N.; Ferreira-Lopes, A.; Gomes, O. (Studies in Nonlinear Dynamics and Econometrics, 2014)
This article analyses the stability properties of the steady-state and the transitional dynamics of an endogenous growth model with human capital, increasing-varieties R&D, and quality-ladders R&D [Strulik, 2005, Review of International Economics, 13 (1): 129-145]. We show that when spillovers within R&D sectors are higher than spillovers across the two R&D sectors, the equilibrium is unstable. However, when spillovers between sectors are higher than within, the equilibrium is a saddle-path. This result emphasizes the need for empirical research that compares quantitatively the importance of these two types of spillovers and highlights the importance of studying intersectoral effects between the two R&D sectors. We describe plausible paths of economic development after changes in crucial parameters and uncover some transitional effects that were impossible to detect in the steady-state analysis. We also show that this model's transition dynamics can mimic the main features of the process of productivity slowdown that began in the 1970's.